The Development of Hots Assessment Instrument using Quizizz During Covid 19 Pandemic in 11th Grade Biology Second Semester - Ananda Anggy Pamelia; Dyah Hariani (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2022)
High Order Thinking Skills (HOTS) require students to have the ability to argue, make decision and solve problem that exist in everyday life. The purpose of this research was describe validity, reliability, and response of students about practicality of Quizizz learning tool as HOTS assessment tool for 11th grade Biology second semester to measure high order thinking skills SMAN 1 Tarik students. This type of development research used the Analysis, Design, Development and Evaluation (ADDIE) model. Data collection methods included validated interviewed, gave tests and student response questionnaires. The validity of assessment was obtained from results of expert validation. Reliability was obtained from results of test items. Student responses of instrument were obtained from the results of the student response sheets. The trial was limited to 30 students of MIPA 6 12th grade in SMAN 1 Tarik. The results showed that the validation of the assessment instruments for multiple choice and essay question type that developed in this study were in highly valid category, the reliability of instrument was 0.62 for the multiple choice question type and 0.83 for essay item type. Quizizz as a tool of HOTS assessment instrument was practice. The results of student responses got 94% of percentage average. The conclusion of this research was assessment instrument of HOTS questions used Quizizz that developed was valid, reliable, and practice for students. This research could be applied in other schools to measure high order thinking skills of students. Keywords: Assessment instrument, high order thinking skills (HOTS), Quizizz